Analisis Implementasi Strategi Pembelajaran Langsung (Direct Instruction) Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran PAI - Irma Yanti Br Ritonga; Rozan Arkhan Daifullah; Gusmaneli . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to analyze the implementation of the direct instruction learning strategy in improving students’ learning outcomes in Islamic Religious Education (PAI). The focus of the study includes: (1) teachers’ planning in applying the direct instruction strategy; (2) the implementation process covering the stages of orientation, presentation, guided practice, and independent practice; (3) an overview of students’ cognitive, affective, and psychomotor learning outcomes; and (4) the supporting and inhibiting factors encountered during its implementation.The study employs a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation. The results indicate that the implementation of a well-planned and systematic direct instruction strategy is able to significantly improve students’ mastery of subject matter, the development of religious attitudes, and their worship skills. The main supporting factors include teacher competence, facilities and infrastructure, and student motivation, while the inhibiting factors are related to the diversity of students’ initial abilities and time constraints.